2011
DOI: 10.1177/00333549111260s210
|View full text |Cite
|
Sign up to set email alerts
|

Using the North Dakota Immunization Information System to Determine Adolescent Vaccination Rates and Uptake

Abstract: Objectives. We described the uptake and coverage rates of meningococcal conjugate vaccine (MCV4); tetanus-diphtheria-acellular pertussis vaccine (Tdap); and quadrivalent human papillomavirus vaccine (HPV4) in North Dakota using the North Dakota Immunization Information System (NDIIS).Methods. We analyzed all available MCV4, Tdap, and HPV4 doses given after vaccine licensure and through December 31, 2009, obtained from the NDIIS to identify trends and patterns in vaccine administration. We analyzed all data by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Several scientific consensus statements, as the American Academy of Pediatrics (31,32) have recommended to consider a booster dose in adolescence. The recent recommendations in immunization schedule suggest that adolescents should receive a single dose of Tdap vaccine instead of Td for booster immunization against tetanus, diphtheria, and Pertussis and the preferred age for Tdap immunizations is 11 through 12 years of age (31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Several scientific consensus statements, as the American Academy of Pediatrics (31,32) have recommended to consider a booster dose in adolescence. The recent recommendations in immunization schedule suggest that adolescents should receive a single dose of Tdap vaccine instead of Td for booster immunization against tetanus, diphtheria, and Pertussis and the preferred age for Tdap immunizations is 11 through 12 years of age (31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…14 Closely corresponding year and birth date criteria (as of September 1, 2009) showed that ASIIS contained 139,747 records of 11-year-olds and 138,634 total 12-year-olds. Registry population overestimates have been observed in other states 12 and may be explained by children who have left the state but remain active in the registry, an issue identified by the American Immunization Registry Association. 15 Vaccine coverage estimates are higher when using the Census population because it is 60% of the registry's population estimate.…”
Section: Discussionmentioning
confidence: 99%
“…In 9 studies (1 published 141 ), IIS records were used to assess potential disparities in vaccination coverage rates by neighborhood ("pockets of need") or population characteristic. #References 109,123,128,129,134,135,137,144,150,165. ated the extent of overimmunization among US children, as documented in 6 Sentinel Site IISs. 114,171,176,178,182,198 IIS-based assessments of age-appropriate and series completion rates were reported in 4 published studies 127,130,144,162 and 5 abstracts.…”
Section: Iis As a Tool For Public Health Decision Supportmentioning
confidence: 99%